Damage of non-steam-cured UHPC under axial compression with and without short-term sustained loading history. (April 2022) - Zhang, Ziyang; Xu, Tengfei; Castel, Arnaud
Abstract: The damage of non-steam-cured ultra-high performance concrete (UHPC) under short-term sustained compression was experimentally investigated. The UHPC specimens were tested under monotonic loading, cyclic loading without a sustained loading history, or cyclic loading with a sustained loading history. The influence of the sustained stress levels and loading age of UHPC was elucidated. The stress-strain history of the specimens was measured. The effect of damage due to the short-term sustained loading history on the mechanical properties of UHPC was analyzed. The fraction of the sustained strains contributing to the damage was calibrated. The micro-cracking propagation within the UHPC is imagined based on non-destructive testing using an ultrasonic wave method and by assessing the nominal Poisson's ratio. The interface between steel fibers and matrix was observed by Scanning Electron Microscope (SEM). The damage occurred for the UHPC specimens under short-term sustained compression when the sustained stress was higher than 0.7 f c ′ . Both the compressive strength and the elastic modulus of the specimens were reduced. When the sustained stress was greater than or equal to 0.8 f c ′, the elastic modulus of the UHPC specimens measured during the reloading phase was considerably reduced. The specimen group subjected to a sustained stress of 0.9 f c ′ with a duration of 128 s experienced a reduction of about 30% in elastic modulus. The damage is statistically independent of the loading age of the UHPC. Damage is characterized by micro-cracking propagation within the UHPC specimens. Microstructural analysis of the interface between steel fibers and matrix shows that under high sustained stress, the bond between the steel fibers and the concrete matrix was impaired by the creep effect and could not prevent the propagation of micro-cracks.